Islam, nationalism and democracy : a political biography of Mohammad Natsir - Kahin, Audrey (NUS Press, 2012)
As Indonesia's leading Muslim politician in the second half of the 20th century, Mohammad atsir (1980-1993) went from heading the country's first post-independence government and largest Islamic political party to spending years in rebellion and in jail under the Soekarno regime. After initially welcoming Soekarno's overthrow in 1965, he became one of the most outspoken critics of the successor Suharto government's increasingly autocratic rule. Natsir's copious writings stretch from his student days in the late colonial period, when his debates with Soekarno over the character of Indonesian nationalism first attracted public attention, to the years immediately preceding his death when his trenchant criticisms brought him the enmity of the Suharto regime. They reveal a man struggling to harmonize his deep Islamic faith with his equally firm belief in national independence and democracy. Drawing from a wide range of materials, including these writings and extensive interviews with the subject, this political biography of Natsir places the important Muslim politician and thinker in the context of a critical period of Indonesia's history, and describes his vision of how a newly independent country could embrace religion without sacrificing its democratic values.